Spatial pattern and weight of seabed marine litter in the northern and central Adriatic Sea. Issue 1 (15th February 2015) - Strafella, P.; Fabi, G.; Spagnolo, A.; Grati, F.; Polidori, P.; Punzo, E.; Fortibuoni, T.; Marceta, B.; Raicevich, S.; Cvitkovic, I.; Despalatovic, M.; Scarcella, G.
Highlights: First assessment of marine litter distribution on the seabed of GSA 17. The manuscript depicts the status of marine litter on a regional scale. Maps are produced either for the overall litter and for the main litter categories. The study identifies the possible sources of some litter items. The results constitute a starting step for marine litter monitoring in the area. Abstract: The present study analyzes spatial distribution and typology of marine litter on the seabed in the FAO Geographical Sub-Area 17 (northern and central Adriatic Sea). Two surveys were conducted during fall 2011 and 2012 and 67 stations were sampled each year. Litter items were collected using the "rapido" trawl, a modified beam trawl commonly used by the Italian fishermen to catch flat fish and other benthic species. Marine litter in the catches was sorted and classified in 6 major categories (plastic, metal, glass, rubber, wood, other). Plastic litter was further subdivided in 3 sub-categories based on its source: fishing nets, aquaculture nets and other. Plastic was dominant in terms of weight followed by metal and other categories. The highest concentration of litter was found close to the coast likely as a consequence of high coastal urbanization, river inflow and extensive navigation associated with the morphological and hydrological features of the basin.